Estimation the Activity of ADA in Individuals with Cataract and Glaucoma - Zainab Thamer Al-Asady (Journal of Madenat Alelem University College, 2012)
The activity of ADA was evaluated in the serum of (40) individuals (15 patients with cataract, 15 patients with glaucoma and 10 individuals as a control). The results showed significant reduction in ADA activity value in individuals with cataract and glaucoma comparing with control (147.86±2.4 Iu/mg), (164.06±2.5 Iu/mg) and (211.29±7.4 Iu/mg) respectively also there is a significant reduction in ADA activity value in individuals with cataract (147.86 ± 2.4) Iu/mg comparing with those with glaucoma (164.06 ± 2.5) Iu/mg that refer the effect of cataract on ADA activity is more than the glaucoma .